The assessment of the economic risks level of sugar beet growing for the farm economy - Josef Pulkrábek; Miroslav Kavka; Vladimír Rataj; Jaroslav Humpál; Ladislav Nozdrovický; Zdeněk Trávníček; Vladimír Pačuta (Agricultural Economics (AGRICECON), 2012)
The risk rate of sugar beet growing was analyzed by using the algorithm for modelling and generating the random numbers based on the conditions determined in advance and the statistical distribution of sugar beets yield, the total costs, earnings and gross profit. On the bases of results of the analysis of economic risks of sugar beet production in years 1995-2009, it follows that the sugar beet growing in all regions is highly risky in the Czech Republic. The subsidy SAPS and TOP-UP per 1 hectare of sugar beet have a positive impact on its economics though not sufficient enough. In practice, it means that it is highly probable that the break-even point will not be achieved and thereby it is highly probable that the fixed costs are not covered and the update of machines is significantly limited. This happens mainly in the marginal regions. If the agricultural companies count on the separate sugar payment, the sugar beet growing is in all regions of the Czech Republic with acceptable risk.